Improving Telekom Malaysia’s customer satisfaction through their staff and business partner / Munawarah M. Sarkawi - M. Sarkawi, Munawarah (Faculty of Business and Management, 2010)
This study is conducted as a partial fulfillment of the coursework of Project Paper (IBM 662). Title of the study is “Improving Telekom Malaysia’s Customer Satisfaction Through Their Staff and Business Partner”. The main objective of the study is to identify the commitment of Telekom Malaysia in order to build the long-term relationship with their customers and business partners, to justify the important of communication skill in this department (TMSME), to explore the effort of the staff in setting the meeting and business activities for their customers and business partner and lastly to clarify the transparency of information provided by them is assisting the customer’s requirements and understandings. This study was conducted under two types of data collection; Primary Data and Secondary Data. The Primary Data was collected discussion with staffs at Telekom Malaysia Berhad Sentosa Johor Bahru, while the Secondary Data was collected from various sources such as internet, magazines, journals, book and articles and newspaper. This case study will highlight certain recommendations which should be noted by Telekom Malaysia Berhad for the future benefit.